Stress Management for the Prevention of Metabolic Diseases in Adolescents - Dhimas Anggi Septiansyah; Nisa Dewanti (Sarana Ilmu Indonesia (salnesia), 2026)
Adolescent stress was identified as a contributing factor that could influence healthy lifestyle behaviors, thereby increasing the risk of metabolic diseases. Adaptive stress management was considered an important strategy for preventing these conditions. This community service program aimed to improve adolescents’ knowledge and skills in adaptive stress management and to screen stress levels and metabolic disease risk. The program employed health education and demonstration methods, along with stress level screening using the validated and reliable Perceived Stress Scale (PSS-10) questionnaire (CFI = 0.950; RMR = 0.085; RMSEA = 0.072; Cronbach’s alpha = 0.862). Metabolic disease risk was assessed using a questionnaire developed by the authors based on risk factor indicators, including family history, dietary patterns, physical activity, lifestyle, family environment, and physical signs and symptoms associated with obesity, insulin resistance, hypertension, and other metabolic disorders. Validity testing indicated that all items were valid (Corrected Item–Total Correlation > 0.30) with good reliability (Cronbach’s Alpha = 0.761). The program was conducted on January 9, 2026, involving 30 twelfth-grade students at SMK Informatika Tulangan, Sidoarjo Regency. The results demonstrated that adolescents showed improved knowledge and skills regarding the educational materials, as reflected in their ability to answer questions and perform demonstrations correctly. Most participants experienced moderate stress levels (23 students; 76.67%) and moderate risk of metabolic disease (22 students; 73.33%). These findings highlight the importance of regular health education and screening programs in schools to support adolescents’ physical and mental health.